2011
DOI: 10.1093/europace/eur322
|View full text |Cite
|
Sign up to set email alerts
|

First prospective, multi-centre clinical experience with a novel left ventricular quadripolar lead

Abstract: The new quadripolar electrode LV lead provides more programming options to address common problems faced when managing CRT patients. Electrical measurements from new vectors are comparable with conventional configurations. Furthermore, 11% of patients in the study suffered PNS on all conventional bipolar vectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 27 publications
2
59
0
1
Order By: Relevance
“…All of these prior studies reported a highly elevated implant success rate for the quadripolar leads, which varied between 95% [8] and 100% [5] of cases. The success rate of quadripolar lead implantation in the first selected vein in this work was greater than that reported in a previous study (85.7% vs. 78% [8]), which could be related to the larger number of patients with history of a previous device in this study (32% vs. 4.8%); some of these previous implantations included a failed conventional lead implant attempt.…”
Section: Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these prior studies reported a highly elevated implant success rate for the quadripolar leads, which varied between 95% [8] and 100% [5] of cases. The success rate of quadripolar lead implantation in the first selected vein in this work was greater than that reported in a previous study (85.7% vs. 78% [8]), which could be related to the larger number of patients with history of a previous device in this study (32% vs. 4.8%); some of these previous implantations included a failed conventional lead implant attempt.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Outcomes using this quadripolar lead have only been reported in a few previous studies, two from the same group (initially with 28 patients [7] and later with 40 [8]), and another from multiple centers, including one where 71 patients were analyzed prospectively [8]. A fourth study represents the only other comparison of a group of 23 patients with bipolar leads to a group of 22 patients with quadripolar leads but included a follow-up period of only 3 months [5].…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study assessing the use of this quadripolar lead, 71 out of 75 patients underwent successful implantation of this lead [3]. The ability to identify a suitable pacing site within a branch of the CS increased from 86% (with a traditional true bipolar configuration) to 97% using 2 or more alternate configurations.…”
Section: Article P 470mentioning
confidence: 99%
“…Quadripolar leads can be implanted distally in the coronary sinus (CS) branch by using a proximal electrode for pacing in a location with acceptable electrical parameters to avoid PNS. 6) However, quadripolar leads cannot escape from PNS when the phrenic nerve and CS branch are parallel and close. We report a case in whom we could avoid PNS by using short-spaced bipolar pacing.…”
mentioning
confidence: 99%